Experiment on numerical conformal mapping of unbounded multiply connected domain in fundamental solutions method. (1st April 2001) - Inoue, Tetsuo; Kuhara, Hideo; Amano, Kaname; Okano, Dai
Abstract : We are concerned with the experiment on numerical conformal mappings. A potentially theoretical scheme in the fundamental solutions method, different from the conventional one, has been recently proposed for numerical conformal mappings of unbounded multiply connected domains. The scheme is based on the asymptotic theorem on extremal weighted polynomials. The scheme has the characteristic called invariant and dual. Applying the scheme for typical examples, we will show that the numerical results of high accuracy may be obtained.